Aptamers as a replacement for antibodies in enzyme-linked immunosorbent assay - Toh, S.Y.; Citartan, M.; Gopinath, S.C.B.; Tang, Thean-Hock (Elsevier, 2015)
The application of antibodies in enzyme-linked immunosorbent assay (ELISA) is the basis of this diagnostic technique which is designed to detect a potpourri of complex target molecules such as cell surface antigens, allergens, and food contaminants. However, development of the systematic evolution of Ligands by Exponential Enrichment (SELEX) method, which can generate a nucleic acid-based probe (aptamer) that possess numerous advantages compared to antibodies, offers the possibility of using aptamers as an alternative molecular recognition element in ELISA. Compared to antibodies, aptamers are smaller in size, can be easily modified, are cheaper to produce, and can be generated against a wide array of target molecules. The application of aptamers in ELISA gives rise to an ELISA-derived assay called enzyme-linked apta-sorbent assay (ELASA). As with the ELISA method, ELASA can be used in several different configurations, including direct, indirect, and sandwich assays. This review provides an overview of the strategies involved in aptamer-based ELASA. (C) 2014 Elsevier B.V. All rights reserved.